KANDUNGAN FITOKIMIA, KLOROFIL DAN BIOMASSA DAUN SEMBUNG (Blumea balsamifera) TERHADAP PENCAHAYAAN - Mamay Maslahat; Nia Yuliani (JURNAL SAINS NATURAL, 2014)
The Influence of Lighting to The Phytochemistry, Chlorophyll and Biomass Content of Sembung Leaves (Blumea balsamifera)        The secondary metabolite compounds on the sembung leaves are an active biopharmaceutical matter. Increase of the bio active production on field condition can be conducted by improving the plant biomass through shade and the period of lighting. The purpose  of this research was to understand the influence of lighting to the phytochemical content, chlorophyll and biomass of sembung leaves that planted in the plantation area, Cogreg, Parung Bogor. The steps of this research consisted of the planting of sembung leaves in different lighting each treatment, the calculation of leaves biomass weight , the preparation of samples, the determination of the water level of samples, the phytochemical test of leaves samples and the analysis of chlorophyll content. Observation of the growth of sembung plants conducted periodically, starting from planting to the harvest. The results of statistical analysis of T test,  on the observation of the growth of plants period I and period II showed that the average of the high and number of leaves differ significantly between plants that use shade and without shade (sig<0.05). The number of leaves sembung biomass planted without shade was heavier than planted with the shade. The water level of sembung leaves sample was 9,5 %. Total chlorophyll level of sembung leaves showed that the total chlorophyll level of the sembung leaves without shade was 15,6319 mg/L, while the total chlorophyll level of the sembung leaves with shade was 20,0982 mg/L. Based on the phytochemical test showed that the secondary metabolite compound which contained in both of sembung leaves sample grown using shade or without shade did not differ significantly to flavonoid, saponin,  glycosides, alkaloids and terpenoid.Keywords: Blumea balsamifera, phytochemistry, chlorophyll, lighting ABSTRAK        Senyawa metabolit sekunder yang terdapat pada daun sembung merupakan bahan aktif biofarmaka. Pemacuan produksi bioaktif tanaman pada kondisi lapang dapat dilakukan dengan meningkatkan biomassa tanaman melalui naungan dan periode pencahayaan. Penelitian ini bertujuan untuk mengetahui pengaruh pencahayaan terhadap kandungan fitokimia, klorofil dan biomassa daun sembung yang ditanam di areal perkebunan Cogreg Parung Bogor. Tahapan penelitian terdiri atas penanaman dengan perlakuan pencahayaan yang berbeda pada setiap petak terpisah, penghitungan bobot biomassa daun, preparasi simplisia, penetapan kadar air simplisia, uji fitokimia simplisia daun dan analisis kandungan klorofil. Pengamatan pertumbuhan tanaman dilakukan secara periodikal dari mulai tanam hingga panen. Hasil statistik Uji T pada pengamatan pertumbuhan tanaman periode I & II menunjukkan bahwa rata-rata tinggi sembung dan jumlah daun berbeda secara signifikan antara tanaman yang menggunakan naungan dan tanpa naungan dengan nilai sig<0,05. Jumlah biomassa daun sembung yang ditanam tanpa naungan menghasilkan berat lebih besar dibandingkan dengan naungan. Kadar air simplisia daun sembung sebesar  9,5 %. Kadar klorofil total daun sembung tanpa naungan dan dengan naungan berturut-turut adalah 15,6319 mg/L dan  20,0982 mg/L. Kandungan senyawa metabolit sekunder simplisia daun sembung adalah  flavonoid, saponin,  glikosida, alkaloid, dan terpenoid.Kata kunci : Blumea balsamifera, fitokimia, klorofil, pencahayaan